Peran Tokoh Lintas Agama Dalam Menerapkan Teologi Kerukunan Pasca Konflik Keagamaan Di Tanjungbalai - Sirait, Bebria Wardah (Program Studi Aqidah dan Filsafat Islam STISA Ash-Shofa Tasikmalaya, 2024)
This paper is motivated by the religious conflict that occurred in Tanjungbalai City in mid-2016, which originated from a misunderstanding and involved Islam and Buddhism. The impact of the conflict was quite large, including the burning of Buddhist houses of worship. Tanjungbalai City is inhabited by people of various religions, making it vulnerable to conflict. To maintain peace after the conflict, interfaith leaders in FKUB Tanjungbalai City are tasked with maintaining a peaceful and harmonious religious life through a theological approach. This research found that, religious relations in Tanjungbalai City before the conflict was peaceful. Tensions only occurred during the conflict and when the conflict ended, cautious and traumatic attitudes could still be felt by society, to avoid conflict from happening again. They see conflicts as cases that can be resolved. Serious efforts were made by the government and the community to rebuild harmony in the implementation of the theology of harmony. Religious leaders reinforce each other's beliefs and instill the values of harmony to their followers, encouraging the formation of a society that respects differences and is able to communicate peacefully. Interfaith leaders actively organize various activities aimed at strengthening interfaith relations such as establishing effective communication between religious communities and teaching the values of diversity-based harmony.